2006
DOI: 10.1136/hrt.2005.077131
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of cardioembolism and patent foramen ovale in patients with stroke and a positive travel history suggesting economy class stroke syndrome

Abstract: Objective: To investigate the frequency of acute stroke in patients with a recent travel history and to analyse risk factors, stroke patterns and presence of a patent foramen ovale (PFO) in this patient group. Design: One-year prospective observational study. Setting: Single-centre study. Methods: Enrolling all patients presenting with a first cerebral ischaemia and complementing the usual history with a standardised travel history. Results: Of 338 patients with acute stroke, 42 had a positive travel history (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…In our study, we found a higher prevalence of PFO in patients with PCS compared to those with ACS, while the presence of traditional risk factors, proportion of cardio-embolic aetiology (category TOAST 2), concomitant atrial fibrillation and coincident atrial septum aneurysms did not differ between young stroke patients with PFO and PCS compared to those with PFO and ACS. Together with the findings from SISIFO [27] and other case-control studies, which reported a higher proportion of PCS in patients with PFO than in those without PFO [34,35,36,37,38,39], our results may indicate a higher proportion of stroke attributable to PFO in PCS than in ACS.…”
Section: Discussionsupporting
confidence: 55%
“…In our study, we found a higher prevalence of PFO in patients with PCS compared to those with ACS, while the presence of traditional risk factors, proportion of cardio-embolic aetiology (category TOAST 2), concomitant atrial fibrillation and coincident atrial septum aneurysms did not differ between young stroke patients with PFO and PCS compared to those with PFO and ACS. Together with the findings from SISIFO [27] and other case-control studies, which reported a higher proportion of PCS in patients with PFO than in those without PFO [34,35,36,37,38,39], our results may indicate a higher proportion of stroke attributable to PFO in PCS than in ACS.…”
Section: Discussionsupporting
confidence: 55%
“…Positive travel history was defined as a travel, mainly in a sitting position, of at least 4 h in duration, and median delay between travel and stroke was 7 days. Patients with positive travel history more frequently had PFO and cardioembolic or cryptogenic strokes, and less frequently conventional stroke risk factors compared with those without travel history [8]. These findings suggest that paradoxal embolism through PFO may be a major cause for travelassociated stroke, and supports previous observations.…”
Section: Discussionsupporting
confidence: 84%
“…In parallel to our analysis, a recent prospective study demonstrated a higher proportion of PFO in stroke patients with PTH compared to stroke patients without positive travel history [13]. Given the higher proportion of PTH in patients with paradoxical embolism, physicians should be aware of the association between paradoxical embolism and recent PTH, not only in air travel but also in train, bus, automobile and in situations with prolonged sitting, such as in front of a computer.…”
Section: Symptoms and Clinical Features Of Pfo-associated Cerebrovascmentioning
confidence: 67%
“…Furthermore the strong association between paradoxical embolism and the presence of PTH was shown to be independent of the other examined clinical symptoms, age and sex. We defined PTH as travel of at least 4 h in duration in mainly a sitting position, in a bus, plain, train or automobile [13]. In our study PTH was found in 13.4% of patients with PFO and 3.4% patients without PFO.…”
Section: Symptoms and Clinical Features Of Pfo-associated Cerebrovascmentioning
confidence: 88%
See 1 more Smart Citation